Imaging Brain Metabolism Using Hyperpolarized 13C Magnetic Resonance Spectroscopy. Issue 5 (May 2020) - Le Page, Lydia M.; Guglielmetti, Caroline; Taglang, Celine; Chaumeil, Myriam M.
Abstract : Aberrant metabolism is a key factor in many neurological disorders. The ability to measure such metabolic impairment could lead to improved detection of disease progression, and development and monitoring of new therapeutic approaches. Hyperpolarized 13 C magnetic resonance spectroscopy (MRS) is a developing imaging technique that enables non-invasive measurement of enzymatic activity in real time in living organisms. Primarily applied in the fields of cancer and cardiac disease so far, this metabolic imaging method has recently been used to investigate neurological disorders. In this review, we summarize the preclinical research developments in this emerging field, and discuss future prospects for this exciting technology, which has the potential to change the clinical paradigm for patients with neurological disorders. Highlights: Hyperpolarized 13 C MRS is an emerging metabolic imaging technique that provides in vivo assessment of enzymatic fluxes after injection of hyperpolarized probes (e.g., [1- 13 C]pyruvate). This technology provides valuable diagnostic and treatment monitoring information in the oncological and cardiovascular fields, where measurement of hyperpolarized pyruvate-to-lactate conversion has been translated to the clinic. The technique has recently been applied preclinically in several non-oncological neurological disorders, successfully detecting metabolic impairment. Valuable metabolic data assessing hyperpolarized pyruvate-to-lactate conversion have been acquired in animal models of multiple sclerosis, traumatic brain injury, neuroinflammation, cognitive impairment, and stroke. Clinical trials on healthy volunteers and traumatic brain injury patients are currently underway.